Field Oriented Economic Model Predictive Control for Permanent Magnet Synchronous Motors. Issue 2 (2020) - Geweth, D.; Zanelli, A.; Frison, G.; Vollmer, U.; Diehl, M.
Abstract: This paper proposes a novel nonlinear model predictive control approach for permanent magnet synchronous machines (PMSM). The optimization problem is formulated as a field oriented economic model predictive control (FO-EMPC) problem and therefore a target selector is not necessary. A dq-model of the PMSM with spherical voltage and current constraints is taken into account. A terminal set and a terminal penalty are introduced to mitigate stability and convergence issues with a short prediction horizon. The performance of the proposed control scheme is demonstrated in a simulation study on a personal computer and in a hardware-in-the-loop simulation, which show that the transition time is reduced by more than one order of magnitude with respect to state-of-the-art approaches, especially when the voltage constraint becomes active.